2020 54th Asilomar Conference on Signals, Systems, and Computers 2020
DOI: 10.1109/ieeeconf51394.2020.9443432
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Neutral Devices: Can Hybrid RF-Acoustic Signals Point Them Out?

Abstract: We present a hybrid signaling approach to position energy-neutral devices. Our method combines the best of two worlds: instant RF signals for both communication and energy transfer, and slower propagating acoustic waves for accurate distance measurements. We introduce advanced energy loading of an 'E-buffer' through beamformed RF signals. The scientific contribution of our approach is twofold, advancing both the positioning performance and the energy harvesting efficiency. On the one hand, we overcome current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Within the Techtile environment, a number of Kema L010 ultrasonic speakers combined with off-the-shelf amplifiers with a frequency range over 45 kHz are mounted on the tile's overlays. These speakers are currently used for RF-acoustic indoor positioning of energy neutral devices [13], [14]. Vice versa, if an ultrasonic speaker based mobile node needs to be localized, a more compact, energy-efficient and omnidirectional speaker is desired, which is not the case with the Kema L010.…”
Section: A Acoustic Sensors and Actuatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the Techtile environment, a number of Kema L010 ultrasonic speakers combined with off-the-shelf amplifiers with a frequency range over 45 kHz are mounted on the tile's overlays. These speakers are currently used for RF-acoustic indoor positioning of energy neutral devices [13], [14]. Vice versa, if an ultrasonic speaker based mobile node needs to be localized, a more compact, energy-efficient and omnidirectional speaker is desired, which is not the case with the Kema L010.…”
Section: A Acoustic Sensors and Actuatorsmentioning
confidence: 99%
“…Mobile nodes in acoustic positioning often consist of microphone modules instead of speakers, as receiving requires less energy than transmitting acoustic signals. Energy-wise, adding RF to the system is a dreadful decision but can be countered by adding RF-energy harvesting hardware on the mobile node side [14]. Another solution can be found by (almost) passive RF-backscattering, where communication is acquired by either reflecting or absorbing the incoming RF waves.…”
Section: B Energy-neutral Hybrid Rf-acoustic Localizationmentioning
confidence: 99%
“…These two voltages are the boundaries on which power will be delivered and are subject to the hybrid RF-acoustic hardware. The capacitance is set to 22 µF according to [11] with V chrdy = 3.10 V, V ovdis = 2.8 V and worst case LDO efficiency η LDO of 74 %. The necessary storage energy to be harvested can be calculated with:…”
Section: B Harvesting Chipsetmentioning
confidence: 99%
“…In previous research [11], we showed that directional, single band wireless power transfer in combination with RF backscattering enables the full passive positioning of a hybrid RFacoustic mobile tag. However, two problems raised, namely the low update rate and the position presumption for directional power transfer.…”
Section: Introductionmentioning
confidence: 99%